The Relationship Between Agility and Speed on Futsal Dribbling - Setyawan, Dicky Budhi; Peking, Intan Marchelina (Athena: Physical Education and Sports Journal, 2023)
The purpose of this study was to obtain data on agility and speed on the ability to dribble futsal extracurricular futsal students at SMP PGRI 12 Cilandak. This research uses a quantitative approach to correlational techniques. The study population was futsal extracurricular students at SMP PGRI 12 Cilandak with a sample of 30 students obtained through random sampling technique.The results showed that there was a positive effect of agility on dribbling, positive effect of speed on dribbling. Agility and speed had a very strong relationship and indicating that it has a significant influence on dribbling. In futsal training, agility and speed can be implemented to enhance dribbling ability.